HPLC determination of theophylline and paracetamol in fresh and powdered milk - Fernandes, T. (2016)
Poster presented at the 1st International Congress of CiiEM - From Basic Sciences to Clinical Research. 27-28 November 2015, Egas Moniz, Caparica, Portugal